Evaluation Study on Rural Telephony (Volume - I) - Planning Commission (Planning Commission, 2010)
The development of rural connectivity through a strong communication network can play a very important role in enhancing the quality of life of rural people. To make every citizen the beneficiary of economic development from liberalization, it is necessary that everyone has equal access to development opportunities in the country. Thus, the effective system of communication through telecom is one of the very important tools to bring about development in rural areas. Rural connectivity comes very close to enablement of the community.
Programme Evaluation Organisation, Planning Commission, Government of India